Scleral crosslinking with riboflavin and ultraviolet A (UVA). A review - M. M. Bikbov; V. K. Surkova; E. L. Usubov; M. N. Astrelin (Oftalʹmologiâ)
Crosslinking is a formation of chemical bonds between large molecules. It makes material stronger. Corneal crosslinking with riboflavin and ultraviolet A (UVA) has been successfully used in keratectasia treatment since 2003. There are some presuppositions of the scleral crosslinking successful using in the progressive myopia, characterized by thinning and mechanical strength decrease of the sclera, as well as in corneal ectasia. Experimental investigations showed an increase in the mechanical strength of the sclera after crosslinking with riboflavin and UVA in vitro. At the same time there were no changes in the thickness of the sclera. Achieved biomechanical effect was constant over a time with interval during up to 8 months in rabbits in vivo. Scleral structure changes after crosslinking were studied with light, electron and atomic force microscopy. Dense collagen bundle at the same time with fibers diameter increase was observed. The spatial pattern of fibrils within crosslinked scleral tissue was tangled and running in different directions. Some authors found such side effects of the procedure as damage of the retina and cornea on the irradiation side because of the high irradiance and thinning of the sclera as a result of dehydration. The optimal duration of riboflavin instillation (20 minutes) and irradiation with 3 mW/cm² (40 minutes) were determined in the experiments. It was shown in vivo, that crosslinking of the sclera with riboflavin and UVA prevented the growth of the rabbit eyes in occlusion-induced myopia. There are several data about successful clinical using of the scleral crosslinking. However, only 6 patients (12 eyes) were observed, procedure parameters are not clear, follow-up period was only 6 months. Thus, now there are many unsolved questions about efficacy and safety of the scleral crosslinking with riboflavin and UVA. Experimental results encourage for a new method of the progressive myopia treatment will be created.